2015
DOI: 10.1007/s13205-015-0298-1
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of petroleum hydrocarbons from crude oil-contaminated soil with the earthworm: Hyperiodrilus africanus

Abstract: A study on the bioremediation potentials of the earthworm Hyperiodrilusafricanus (Beddard) in soil contaminated with crude oil was investigated. Dried and sieved soils were contaminated with 5 ml each of crude oil with replicates and inoculated with earthworms and monitored daily for 12 weeks. Physicochemical parameters such as pH, total organic carbon, sulfate, nitrate, phosphate, sodium, potassium, calcium and magnesium were determined using standard procedures. Total petroleum hydrocarbon (TPH) was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 26 publications
7
25
0
Order By: Relevance
“…High EC value decreases microbial soil activities [29], therefore the reduction in EC values (Table 2) during biodegradation in this present study could be due to the increased activities of diesel oil utilizing bacteria in the soil and leaching out the salt content. This result correlates with the findings of Ekperusi and Aigbodion [30] who reported that EC of soil highly increased after contamination of soil with diesel oil and heavy metals, and gradually decreased with the incubation of earthworm. Christopher et al [31] reported that the EC of crude oil contaminated soil could be as high as 3320 µS/cm which could hinder microbial growth.…”
Section: Electrical Conductivity Of Soil During Diesel Oil Biodegradasupporting
confidence: 91%
See 1 more Smart Citation
“…High EC value decreases microbial soil activities [29], therefore the reduction in EC values (Table 2) during biodegradation in this present study could be due to the increased activities of diesel oil utilizing bacteria in the soil and leaching out the salt content. This result correlates with the findings of Ekperusi and Aigbodion [30] who reported that EC of soil highly increased after contamination of soil with diesel oil and heavy metals, and gradually decreased with the incubation of earthworm. Christopher et al [31] reported that the EC of crude oil contaminated soil could be as high as 3320 µS/cm which could hinder microbial growth.…”
Section: Electrical Conductivity Of Soil During Diesel Oil Biodegradasupporting
confidence: 91%
“…The reduction in heavy metals as shown in Table 3 could be due to sorption of heavy metals by soil microorganisms basically bacteria and fungi in the formation of oxides, hydroxides, carbonates, exchangeable cations, and or bound to organic matter in the soil [32]. A corresponding significant decrease in the heavy metals concentration with Eudrilus eugeniae after 30, 60 and 90 days was reported by Ekperusi and Aigbodion [30]. Similarly, reduction in heavy metal (cadmium and lead) content of hydrocarbon contaminated soil was observed by Lang et al [33].…”
Section: Reduction In Heavy Metal Concentrationmentioning
confidence: 75%
“…United States National Research Council classified these organic contaminants into high and low molecular weight hydrocarbons, oxygenated, halogenated aliphatics, aromatics, nitro aromatics hydrocarbons and alkanes (NRC 2000;Abrajano and Yan 2014). These hydrocarbons and alkanes have been considered as priority pollutants (NRC 2000;Ekperusi and Aigbodion 2015), which are biohazards and biomagnified in the environment (Kramer and Van der Heijden 1990;Mohamed et al 2006). While, there are special group of microorganisms that can biodegrade and biotransform these hydrocarbons and alkanes to assimilate as biomass in the ecosystem (Chikere et al 2012;Rajasekar et al 2012;Roy et al 2015;Kumar et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Free radical is the most common reactive oxygen species in human (Georgewill and Nwankwoala, 2008). Once polyaromantic hydrocarbons enter the body of a living organism, each are metabolized to form highly reactive molecules such as diol epoxides that are polyromantic hydrocarbons intermediate metabolites that causes oxidative stress (Ekperusi and Aigbodion, 2015;Penning, 2014).…”
mentioning
confidence: 99%